PENGARUH PROFITABILITAS SOLVABILITAS DAN OPINI AUDIT TERHADAP AUDIT DELAY - Rohana, Rohana Rohana (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2020)
ABSTRACTThis study aims to determine the influence of profitability, solvency and audit opinion to audit delay in infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange in the 2016-2018 period. The independent variables used in this study are profitability, solvency and audit opinion. And the dependent variable used is audit delay. The data used in this study are secondary data obtained from the Indonesia Stock Exchange 2016-2018. The sample is determined using the purposive sampling method. This study amounted to 105 samples from 35 companies.The results of this study indicate that profitability does not affect audit delay with significance 0.345> 0.05. Solvability does not affect audit delay with a significance level of 0.619> 0.05, while auditor opinion has a negative effect on audit delay with a significance of 0,00 <0,5. Profitability, solvency and audit opinion simultaneously have a significant effect on audit delay with a significance value of 0,000 less than 0.05. Keywords : Profitability, Solvency, Audit Opinion, Audit Delay DAFTAR PUSTAKAAlthaf, Fauziyah. (2016). Pengaruh Ukuran Perusahaan, Profitabilitas, Opini Auditor, dan Umur Perusahaan terhadap Audit Delay. Jurnal Nominal Vol.1. Universitas Negeri Yogyakarta.Amani,Fauziyah Althaf. (2016). Pengaruh Ukuran Perusahaan, Profitabilitas, Opini Audit, Dan Umur Perusahaan Terhadap Audit Delay (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia pada Tahun 2012-2014). Jurnal Nominal / Volume V Nomor 1Andini, Widya Herliana. (2016). Faktor-Faktor yang Berpengaruh Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014. Skripsi, Universitas Bakrie, Jakarta.Ani, Yulianti. (2011). Faktor-faktor yang Berpengaruh terhadap Audit Delay (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun (2007-2008). Skripsi. Yogyakarta: Universitas Negeri Yogyakarta.Apriana, Nurahman. (2017). Pengaruh Profitabilitas, Solvabilitas, Ukuran Perusahaan, dan Ukuran Kap Terhadap Audit Delay pada Perusahaan Properti dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015. Skripsi.Universitas Negeri Yogyakarta.Arens, Alvin A., Rendal J.Elder dan Mark S.Beasley, (2012), Jasa Audit dan Assurance: Pendekatan Terpadu (Adaptasi Indonesia), Buku 1, Alih Bahasa : Amir Abadi Jusuf, Salemba Empat, Jakarta.Aryaningsih, N.N.D, dan Budiartha I Ketut. (2014).